Highly dispersible and magnetically recyclable poly(1-vinyl imidazole) brush coated magnetic nanoparticles: an effective support for the immobilization of palladium nanoparticles. (21st December 2015) - Pourjavadi, Ali; Safaie, Niloofar; Hosseini, Seyed Hassan; Bennett, Craig
Abstract : A heterogeneous recoverable catalyst was prepared via the complexation of palladium onto the surface of magnetic nanoparticles coated by a poly(1-vinyl imidazole) brush. Abstract : A heterogeneous recoverable catalyst was prepared via the complexation of palladium onto the surface of magnetic nanoparticles coated by a poly(1-vinyl imidazole) brush. The stable, active and reusable catalyst was proven to be highly active in aerobic oxidation of primary and secondary alcohols with excellent yields. Only 0.1 mol% of the catalyst was used to oxidize 1 mmol of primary and secondary alcohols. The catalyst was readily recovered and reused up to 10 times under the described reaction conditions without significant loss of activity.